2013
DOI: 10.1128/jb.00659-13
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of mRNA Degradation in Borrelia burgdorferi

Abstract: The importance of gene regulation in the enzootic cycle of Borrelia burgdorferi, the spirochete that causes Lyme disease, is well established. B. burgdorferi regulates gene expression in response to changes in environmental stimuli associated with changing hosts. In this study, we monitored mRNA decay in B. burgdorferi following transcriptional arrest with actinomycin D. The timedependent decay of transcripts encoding RNA polymerase subunits (rpoA and rpoS), ribosomal proteins (rpsD, rpsK, rpsM, rplQ, and rpsO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 59 publications
1
17
0
Order By: Relevance
“…(a) Northern blot analyses of total RNA isolated from wild-type (WT), ssrS mutant (ssrS null) and ssrS complemented (ssrS comp) strains temperature-shifted from 23°C and grown at 35°C until mid-log phase. RNA was separated on an 0.8% agarose gel, transferred to membranes and hybridized with 32 P-labeled probes to ospC, ospA, dbpA and flaB mRNA ( Archambault et al, 2013;Fraser et al, 1997). We found that processing of both the 5′ and 3′ ends of Bb6S RNA requires the endoribonuclease RNase Y (Figure 3e,f).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…(a) Northern blot analyses of total RNA isolated from wild-type (WT), ssrS mutant (ssrS null) and ssrS complemented (ssrS comp) strains temperature-shifted from 23°C and grown at 35°C until mid-log phase. RNA was separated on an 0.8% agarose gel, transferred to membranes and hybridized with 32 P-labeled probes to ospC, ospA, dbpA and flaB mRNA ( Archambault et al, 2013;Fraser et al, 1997). We found that processing of both the 5′ and 3′ ends of Bb6S RNA requires the endoribonuclease RNase Y (Figure 3e,f).…”
Section: Discussionmentioning
confidence: 91%
“…6S RNA is processed from a larger transcript in E. coli by mechanisms involving RNase BN or the endoribonucleases RNase G and RNase E (Chen, Dutta, & Deutscher, ; Kim & Lee, ) and further trimmed by exoribonucleases RNase T and RNase PH (Li, Pandit, & Deutscher, ). B. burgdorferi has a limited repertoire of ribonucleases, compared to E. coli and B. subtilis , and lacks genes encoding RNase G and RNase E; the only predicted endoribonuclease homologs are RNase III, RNase M5, RNase P, RNase Y, RNase Z, YbeY and RNase HII (Anacker, Drecktrah, LeCoultre, Lybecker, & Samuels, ; Archambault, Borchert, Bergeron, Snow, & Schlax, ; Fraser et al, ). The size of Bb6S RNA was assayed by Northern blot in individual RNase mutant strains to investigate Bb6S RNA processing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It also indicates that T porA affects MOMP expression in C. jejuni. (50,51). The intrinsic resistance is primarily due to the function of the CmeABC efflux system (52,53).…”
Section: Introductionmentioning
confidence: 99%